Organizational Culture - Vveinhardt, Jolita (IntechOpen, 2018)
It is stated that the concept of organizational culture reveals that the behavior of people in organizations is highly influenced by the established attitudes and values of their members, and objective characteristics of organizational culture are everything that exists regardless of its members' thoughts. A lot of researchers of organizational culture continue to look for answers about these relationships. Thus, organizational culture is a phenomenon that constantly receives both researchers' and practitioners' attention. This book supplies the reader with a comprehensive overview of the latest results of studies carried out by scientists from different countries. A lot of attention is given to role of national cultures, organizational culture as a determinant of competitiveness, organizational structures, model of culture for innovation, transformational leadership, leadership competencies, project activity etc.